THE INFLUENCE OF RETURN ON EQUITY (ROE) ON PRICE TO BOOK VALUE (PBV) IN FOOD AND BEVERAGE SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Hasbudin; Sulvariany Tamburaka; Ayu Dyah; La Angga (Jurnal Akuntansi dan Keuangan, 2024)
This research aims to determine and analyze the effect of Return On Equity (ROE) on Price To Book Value (PBV) in manufacturing companies in the Food and Beverage sub-sector listed on the Indonesian Stock Exchange. The population in this research is the food and beverage subsector manufacturing companies totaling 47 companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The sampling method in this research used a purposive sampling technique, so that 13 samples were obtained from 47 companies. The data collection method uses documentation. The research uses a quantitative approach with data analysis methods using simple regression analysis with the help of the IBM SPSS 25 application. The results of this research show that Return On Equity has a significant positive effect on Price to Book Value in Food and Beverage companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022.